A stable approach for coupling multidimensional cardiovascular and pulmonary networks based on a novel pressure‐flow rate or pressure‐only Neumann boundary condition formulation. (14th November 2013) - Ismail, M.; Gravemeier, V.; Comerford, A.; Wall, W.A.
SUMMARY In many biomedical flow problems, reversed flows along with standard treatment of Neumann boundary conditions can cause instabilities. We have developed a method that resolves these instabilities in a consistent way while maintaining correct pressure and flow rate values. We also are able to remove the necessary prescription of both pressure and velocities/flow rates to problems where only pressure is known. In addition, the method is extended to coupled 3D/reduced‐D fluid and fluid‐structure interaction models. Numerical examples mainly focus on using Neumann boundary condition in cardiovascular and pulmonary systems, particularly, coupled with 3D‐1D and 3D‐0D models. Inflow pressure, traction, and impedance boundary conditions are first tested on idealized tubes for various Womersley numbers. Both pressure and flow rate are shown to match the analytical solutions for these examples. Our method is then tested on a coupled 1D‐3D‐1D artery example, demonstrating the power and simplicity of extending this method toward fluid‐structure interaction. Finally, the proposed method is investigated for a coupled 3D‐0D patient‐specific full lung model during spontaneous breathing. All coupled 3D/reduced‐D results show a perfect matching of pressure and flow rate between 3D and corresponding reduced‐D boundaries. The methods are straight‐forward to implement in contrast to using Lagrange multipliers as previously proposed in other studies. Copyright © 2013 John Wiley & Sons, Ltd.